2006
DOI: 10.1136/emj.2005.028969
|View full text |Cite
|
Sign up to set email alerts
|

Is atropine needed with ketamine sedation? A prospective, randomised, double blind study

Abstract: Objective: To compare atropine with placebo as an adjunct to ketamine sedation in children undergoing minor painful procedures. Outcome measures included hypersalivation, side effect profile, parental/ patient satisfaction, and procedural success rate. Methods: Children aged between 1 and 16 years of age requiring ketamine procedural sedation in a tertiary emergency department were randomised to receive 0.01 mg/kg of atropine or placebo. All received 4 mg/kg of intramuscular ketamine. Tolerance and sedation sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 19 publications
5
45
2
2
Order By: Relevance
“…Our finding of less vomiting with atropine relative to either glycopyrrolate or no anticholinergic supports the supposition of Heinz et al 3 that atropine has mild antiemetic properties. Based on our data the number needed to treat to prevent one child from vomiting would be 16.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our finding of less vomiting with atropine relative to either glycopyrrolate or no anticholinergic supports the supposition of Heinz et al 3 that atropine has mild antiemetic properties. Based on our data the number needed to treat to prevent one child from vomiting would be 16.…”
Section: Discussionsupporting
confidence: 89%
“…1,2 Their efficacy in this role is controversial, with study results both pro 3 and con. 2,4,5 It is possible that the conflicting evidence on this issue results from differences between the two anticholinergics typically used-atropine and glycopyrrolate.…”
mentioning
confidence: 99%
“…Numerous studies and randomized controlled trials (RCTs) on the use of ketamine show a favorable safety profile, with a low risk of airway complications and emergence phenomena. [1][2][3][4][5][6][7][8][9][10] One of the key disadvantages of ketamine, however, is the long recovery period. The optimal parenteral mode of ketamine administration-intravenous (IV) versus intramuscular (IM)-has been discussed in only a small number of studies and reviews in terms of time to discharge and its relationship to the incidence of adverse events.…”
mentioning
confidence: 99%
“…Atropine has the potential to cause central toxicity which may complicate the management of cardiomyopathy (11). It has been reported that atropine may cause aspiration pneumonia through induction of the swallowing disorder and inhibition of the cough reflex (12), and it is associated with a higher incidence of a transient rash (13).…”
Section: Introductionmentioning
confidence: 99%